Pembangunan Modul Dokumentasi Aplikasi Point Of Sale Odoo Berbasis Web Di PT Belant Persada: The Development of Application Documentation Module Point of Sale Odoo Based on Web at PT Belant Persada - Puji Dwi Gustiani; Rina Trisminingsih; Lufty Abdillah (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2018)
ABSTRACT Odoo is an open source ERP application where there are various business programs such as Sales, Point of Sale, CRM, Human Resources, Finance and Accounting and others. One application module developed by Odoo is Point of Sale. Point of sale (POS) is a system that can help the transaction process in a business that is engaged in sales such as supermarkets, restaurants, clothing stores and so others. The use of the Odoo POS application among Indonesian people still sounds not familiar because of the lack of information related to the use of the Odoo POS application. Documentation from the Odoo POS application is available on the Odoo websiteHowever, the documentation does not yet have the function to download documentation files and has not been displayed visually in video format. From this, there is a need for documentation using the Odoo POS application that can download documentation files and display documentation visually in video format to distinguish between the original POS Odoo application documentation module and the Odoo POS application documentation module that the author made. For this reason, was built Application Documentation Module Point of Sale Odoo Based on Web at Pt Belant Persada. The Odoo POS application documentation module contains documentation about the use of the POS Odoo application for retail and restaurant fields and this documentation can be downloaded freely in PDF format and displays the documentation visually in video formatThe method used in the development of the Odoo POS application documentation module is the prototype method. This method has five stages is Communication, Quick Plan, Modeling Quick Design, Construction of Prototype, and Deployment, Delivery, & Feedback. ABSTRAK Odoo adalah aplikasi ERP bersifat open source yang di dalamnya terdapat berbagai program bisnis seperti Sales, Point of Sale, CRM, Human Resource, Finance and Accounting dan lain sebagainya. Salah satu modul aplikasi yang dikembangkan oleh Odoo yaitu Point of Sale. Point of sale (POS) merupakan sebuah sistem yang dapat membantu proses transaksi pada suatu bisnis yang bergerak di bidang penjualan seperti toko swalayan, restoran, toko baju dan lain sebagainya. Penggunaan aplikasi POS Odoo di kalangan masyarakat Indonesia masih terdengar asing karena minimnya informasi terkait penggunaan aplikasi POS Odoo. Dokumentasi dari aplikasi POS Odoo sudah ada di website Odoo. Namun, dokumentasi tersebut belum mempunyai fungsi untuk mengunduh file dokumentasi dan belum ditampilkan secara visual dalam format video. Dari hal tersebut, perlu adanya suatu dokumentasi penggunaan aplikasi POS Odoo yang dapat mengunduh file dokumentasi dan menampilkan dokumentasi secara visual dalam format video untuk membedakan antara modul dokumentasi aplikasi POS Odoo yang asli dengan modul dokumentasi aplikasi POS Odoo yang penulis buat. Untuk itu, dibangunlah Modul Dokumentasi Aplikasi Point of Sale Odoo Berbasis Web di PT Belant Persada. Modul dokumentasi aplikasi POS Odoo berisi tentang dokumentasi penggunaan aplikasi POS Odoo untuk bidang retail dan restaurant serta dokumentasi ini dapat diunduh dalam format PDF secara bebas dan menampilkan dokumentasi secara visual dalam format video. Metode yang digunakan dalam pembangunan modul dokumentasi aplikasi POS Odoo adalah metode prototipe. Metode ini mempunyai lima tahapan yaitu Communication, Quick Plan, Modelling Quick Design, Construction of Prototype, dan Deployment, Delivery, & Feedback.